If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 6y + 9x = 0 Reorder the terms: 5x + 9x + 6y = 0 Combine like terms: 5x + 9x = 14x 14x + 6y = 0 Solving 14x + 6y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6y' to each side of the equation. 14x + 6y + -6y = 0 + -6y Combine like terms: 6y + -6y = 0 14x + 0 = 0 + -6y 14x = 0 + -6y Remove the zero: 14x = -6y Divide each side by '14'. x = -0.4285714286y Simplifying x = -0.4285714286y
| -330=10(-5x-3) | | 4x+8x+6x-24=x | | 5-(3-x)=6.5 | | M=682287/967540 | | -10(X-6)=6(10+2X) | | -4x+4(3x-13)=-140 | | 4x+8x+6x=24 | | -4(3-3m)=-37+7m | | 2(g-h)=b+y | | 9/7*-9/5 | | x^4-2x^3+14x^2-18x+45=0 | | 8k-k-5k+7-2k= | | -15+x+1=31 | | -4(2u-6)=-4-12u | | (6/5x)-(5/8)=(3/4x) | | -12-8(x-3)=-6(x-1) | | 6x-11x-12=-3(x-2) | | -(1+8X)=6-9X | | -9(10x+11)=351 | | 4-2y-y=2 | | tanx=(3/2)^(1/3) | | d=7+5x-8x | | 2x=1.8 | | 6-5x=9x-10x-6 | | 3x+7=8x-63 | | -12=-7–7/2s | | 14+7K=9K-2 | | -8(10x+3)=376 | | f(x)=4x^2-24x+31 | | 19v=-114 | | 3+4(x+6)=11 | | -9=2/3x–17 |